PENGELOLAAN SAMPAH ORGANIK MENJADI PUPUK KOMPOS DI DESA SUMBERSARI - Nabila Aulia Naufa; Rinda Siaga Pangestuti; Rusham Rusham (Universitas Islam 45 Bekasi, 2023)
Garbage is something that is useless and unwanted. Garbage that is not managed properly can cause environmental and health problems. One way to overcome the negative impact of waste is to process community-based waste. Household organic waste needs to be addressed with waste management using simple methods, one of which is composting. The purpose of this service is to increase community knowledge and skills to manage household organic waste into compost. Community service activities were carried out in Hamlet III, Sumbersari Village, Pebayuran District, Bekasi Regency. The composting process was carried out in a 15L composter using EM-4 bioactivator. The results of this service are increasing public understanding of the procedures for making organic compost from household organic waste and increasing public awareness in waste management.